EXAMINING THE PERCEPTIONS AND EXPERIENCES OF LABORATORY SPECIALISTS AND TECHNICIANS ON THE IMPLEMENTATION OF A NEW LABORATORY INFORMATION SYSTEM: A PHENOMENOLOGICAL STUDY - Ahmed Mithqal Alshammari , Fidaa Alaswad Almutairi, Faisal Gharbi Alharbi, Dalal Fahad Aldhafery, Ahmad Hamoud Almutairi, Wafa Sakil Al Hazing (Chelonian Research Foundation, 2022)
Background: Laboratory information systems (LIS) play a crucial role in the efficient management of laboratory data and workflows. The implementation of a new LIS can have a significant impact on the perceptions and experiences of laboratory specialists and technicians. Objective: To explore the perceptions and experiences of laboratory specialists and technicians regarding the implementation of a new LIS in their workplace. Methods: A qualitative phenomenological study was conducted using semi-structured interviews with a purposive sample of 20 laboratory specialists and technicians who had experienced the implementation of a new LIS in their laboratory. Interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis. Results: Four main themes emerged from the data: (1) initial reactions and expectations, (2) challenges and barriers during implementation, (3) perceived benefits and improvements, and (4) recommendations for future implementations. Participants reported mixed initial reactions, ranging from excitement to apprehension. Challenges included training issues, technical problems, and resistance to change. Perceived benefits included improved data accuracy, streamlined workflows, and enhanced communication. Participants recommended better training, more user involvement, and continuous support for successful LIS implementations. Conclusion: The implementation of a new LIS evokes various perceptions and experiences among laboratory specialists and technicians. Understanding these perspectives can help guide future LIS implementations and optimize the benefits for laboratory staff and patient care.